Development of natural gum based glipizide mucoadhesive microsphere - Al Mamun, A.; Bagchi, M.; Amin, L.; Sutradhar, K.; Huda, Naz (Medipoeia Publication, 2014)
The objective of this study was to develop glipizide microsphere with natural gums. Guar gum and xanthan gum were used separately in different ratios as natural polymers. The microspheres were prepared by orifice ionic gelation method and they were characterized by scanning electron microscopy and particle size analysis. Among six formulations, microspheres of four formulations (F1-F4) were discrete, spherical and free flowing. There was an inverse relationship found between the amount of gum and surface smoothness in case of guar gum-containing microspheres while a forward relationship was found between amount of gum and surface smoothness in case of the microspheres containing xanthan gum. The size of the particles increased with increasing amounts of gum. It can be concluded that guar gum and natural gum at a ratio of 1:0.25 and 1:0.5 can be ideal for formulating natural gum based glipizide mucoadhesive microsphere.